PENGARUH KOMPETENSI PEDAGOGIK GURU DAN MUTU PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA - Yani, Ahmad; Tamyiz; Roni, Abdul (UNISAN JURNAL, 2023)
The purpose of this study was carried out to determine the teacher's pedagogic competence and the quality of learning on student learning outcomes. The research design uses quantitative. Quantitative research is research based on the philosophy of positivism, reality is seen as something concrete, can be observed with the five senses, can be categorized according to type, shape, color and behavior, does not change, can be measured and verified. The research was conducted at Teladan Jaya Lempuing OKI Senior High School. The sampling technique in this study used a total sampling technique in which the sample in this study were all fifth grade students, totaling 25 students at Teladan Jaya Lempuing OKI High School. The results of this study found that there was an effect of teacher pedagogic competence and learning quality on student learning outcomes of SMA Teladan Jaya Lempuing OKI by using the linear regression formula. Because Fcount > Ftable, then H0 is accepted, so it can be concluded that the teacher's pedagogic competency score and learning quality have an effect on student learning outcomes greater than r table at a significant 5% (0.414> 0.413).